EFFECT OF COVER CROPPING ON PREVENTION OF RUN OFF AND SOIL LOSS UNDER SLOPELAND CONDITION IN RED AND BLACK SOIL OF NORTH CENTRAL PLATEAU ZONE OF ORISSA - Sahu, S.K. (Journal of Soil and Water Conservation, 2022)
The Investigation was carried out at Regional Research Station, Keonjhar to study the effect of cover cropping on run off and soil loss under identical slope condition (5%) for red and black soil. The results indicated that irrespective of the treatments, the run-off and soil loss were maximum in the month of August due to highest amount of rainfall (40.40%) during this month, compea intercrop with sunflower resulted the highest conservation of soil to the time of 19.4 per cent and 26.5 per cent for red and black soils from 16.1 per cent to 19.4 per cent under the red soil condition while the decrease ranged from 12.5 per cent to 25.4 per cent under black soil condition. Ladies finger and sunflower, owing to longer canopy at early stage give a good soil cover, checked beating action of rain drops and decreased splash erosion. In general productivity was higher in black soil as compared to red soil. Inclusion of cowpea as an intercrop with sunflower conserved soil further to an extent of 2.6 tonnes per ha. in red soil and 2.7 tonnes per ha. in black soil. Cowpea intercrop with ladies finger was found to be most remunerative in both the soils.